PENGARUH SUBSTITUSI CANGKANG KEMIRI PADA SEBAGIAN AGREGAT HALUS UNTUK BETON K-250 TERHADAP KUAT TEKAN - Syafitri Syafitri; Surya Eka Priana; Febrimen Herista (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Concrete is one of the most widely used materials in the construction industry. Concrete building blocks are materials that are widely found in nature, including sand and gravel and cement constituents. Candlenut shell is one of the additives or substitutes for aggregate which has recently been used. began to investigate the impact of its use on the mixture in concrete. The use of candlenut shells can be treated as a substitute for coarse or fine aggregate depending on the size of the pecan shell grains used. and to determine the optimum compressive strength of concrete by mixing candlenut shells as a partial substitute for fine aggregate with a percentage of 0%, 10%, 20%o and 30% of the weight of the fine aggregate. The research method is testing the compressive strength of concrete samples by carrying out laboratory test result. From the results of the concrete experiments that have been carried out and the data that has been obtained with the normal quality of fc 20.75 Mpa concrete and concrete with candlenut shell substitution for coarse aggregate in a mixture of 10%, 20%, and 30%, there are several conclusions, namely the age of concrete is 7, 14.28 days of mixed concrete of 10%, 20%, and 30% of the compressive strength experienced a decrease in the normal concrete compressive strength in every variation of the percentage. The results of the research of normal concrete and candlenut shell mixture on normal concrete 7,14,28 days are 10,74 MPa,13,86 MPa. 14.42 MPa, in 10% candlenut shell mixture 7.14.28 days which is 7.35 MPa. 10.75 MPa. 11.03 MPa, in the mixture of 20%% candlenut shells 7.14.28 days, namely 6.19 MPa, S.48 MPa 9.33 MPa, and in the mixture of 30%% candlenut shells, which is 6.79 MPa. 7,36 MPa, 8,77 Mpa/ Use candlenut shell for partial substitution of fine aggregate in concrete cannot be used as a material as a constituent of concrete.